SESAR LEMBANG DAN RESIKO KEGEMPAAN - -, Agung Muljo; -, Faisal Helmi (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
Lembang is located 30 kilometers from Bandung city, in fact, Lembang is one of the area which has earthquake gristle. Pursuant to result of remote sensing image that Lembang area passed by a long normal fault. Lembang Fault represent most potential for rock movement, this matter is caused by fault path represent a place that waving the earthquake. If the earthquake happen, the area along fault zone experience of bigger vibration. Strategic location which reside in in Lembang fault zona are Lembang Town, Market place, touris location of Maribaya, settlement area and etcetera.